Relationship between resting heart rate and arterial stiffness in patients with chronic obstructive pulmonary disease: Implications for pulmonary rehabilitation. Issue 2 (2nd April 2020) - Sima, Carmen A.; van Eeden, Stephan F.; Reid, W. Darlene; Sheel, Andrew W.; Benari, Ori; Kirkham, Ashley R.; Camp, Pat G.
Abstract: RATIONALE: Pulse wave velocity (PWV), as a measure of arterial stiffness, has been shown to be associated with resting heart rate (RHR) in general population studies. Yet, the evidence on this relationship in chronic obstructive pulmonary disease (COPD) is scarce and contradictory. OBJECTIVES: We examined the relationship between RHR and PWV and explored the effect of standard pulmonary rehabilitation (PR) on these parameters in COPD. METHODS: A two-phase project was conducted. In Phase 1, a cross-sectional study was performed in 55 COPD and 41 control (CTL) individuals. In Phase 2, an interventional study was performed in COPD patients (n = 27) who completed PR. RHR and PWV were assessed using a SphygmoCor device. RESULTS: COPD patients displayed higher RHR (67 ± 11 beats/min vs. 60 ± 9 beats/min, p  = 0.002) and PWV (9.9 ± 1.9 vs. 8.7 ± 2.1 m/s, p  = 0.004) than CTL individuals. Multivariate analysis showed that RHR was significantly associated with PWV in both CTL and COPD groups. However, age and pulse pressure played a moderating role in the RHR-PWV relationship in COPD. After PR, PWV (10.3 ± 2.5 m/s vs. 9.6 ± 2.0 m/s, p  = 0.004), but not RHR (65 ± 10 beats/min vs. 66 ± 9 beats/min, p  = 0.163) decreased. The effect of PR on PWV was maintained even in the presence of confounding factors. CONCLUSIONS: The relationship between RHR and PWV in COPD depends on the age and pulse pressure levels. A standard PR program reduces PWV but does not impact the RHR-PWV relationship in COPD.